The griffin and the dinosaur : how Adrienne Mayor discovered a fascinating link between myth and science - Aronson, Marc (National Geographic, 2014)
Traces the research scientist co-author's explorations in Greece and the Gobi Desert for the origins of the mythical griffin, relating the story of the ancient Scythians and the griffins that were said to have guarded their treasure.